Integration of E-learning into the Physiology Education of Medical Students in their Pre-clinical Curriculum : E-learning in Medical Phyiology Education - Menon, Bindu; Patel, Radha; Kovacs, Kelly; Prevette, Christopher; Chen, Tian; Matus, Coral D (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Purpose: In our institution, we initiated integrated learning in the format of Learning Modules (LM), interactive audio/visual modules developed by the faculty in alignment with session learning objectives, as pre-work for in-class sessions.?This pilot study examined students’ perceptions of this new learning method and effectiveness in helping them achieve content mastery. Methods: The instructor provided the LMs in advance, allowing a self-paced introduction of critical concepts that were subsequently discussed in detail during the in-class learning (ICL) session. A cognitive diagnostic assessment was used to analyze the student’s performance on the exams. This involved identifying six skills, one or more of which were marked to be necessary for answering each exam question correctly. A question-by-skill Q-matrix was constructed, followed by analysis using a Deterministic Input, Noisy "And" Gate (DINA) model. Results: 70% of the students rated the new approach as "Excellent or Good." 63% of the students attained skills necessary to answer questions that involved integrating information gained separately from LM and ICL sessions. However, only 23% of the students achieved mastery in all the 6 skills. Conclusion: This integrative learning system allowed for time optimization since ICL sessions could focus on more interactive aspects of the content.